FAKTOR-FAKTOR YANG MEMPENGARUHI SISA HASIL USAHA (SHU) KOPERASI, USAHA KECIL DAN MENENGAH (UKM) KALIMANTAN TENGAH - sunarmi . sunarmi; Pamungkur . Pamungkur (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2024)
The aim of this research is to determine the factors that influence the remaining results of cooperative businesses in Central Kalimantan province. The dependent variable in this research is Remaining Business Results. The independent variables in this research are Number of Members, Own Capital, Loan Capital, and Business Volume. The data analysis method used is the Error Correction Model (ECM). This research uses secondary data and annual time series data with a research period of 30 years, starting from 1994 to 2023. Based on the research results, it can be concluded that in the long term the number of members and capital themselves have a significant effect on the remaining business results. , while loan capital and business volume have no effect on the remaining business results. In the short term, the number of members and own capital do not affect the remaining business results, while loan capital and business volume influence the remaining business results.